Estimating the impact of somatic cell count on the value of milk utilising parameters obtained from the published literature. Issue 2 (May 2014) - Geary, Una; Lopez-Villalobos, Nicolas; O'Brien, Bernadette; Garrick, Dorian J; Shalloo, Laurence
<x content-type="archive" xml:space="preserve">Abstract</x> The impact of mastitis on milk value per litre independent of the effect of mastitis on milk volume, was quantified for Ireland using a meta-analysis and a processing sector model. Changes in raw milk composition, cheese processing and composition associated with increased bulk milk somatic cell count (BMSCC) were incorporated into the model. Processing costs and market values were representative of current industry values. It was assumed that as BMSCC increased (i) milk fat and milk protein increased and milk lactose decreased, (ii) fat and protein recoveries decreased, (iii) cheese protein decreased and cheese moisture increased. Five BMSCC categories were examined from ⩽100 000 to >400 000 cells/ml. The analysis showed that as BMSCC increased the production quantities reduced. An increase in BMSCC from 100 000 to >400 000 cells/ml saw a reduction in net revenue of 3·2% per annum (€51·3 million) which corresponded to a reduction in the value of raw milk of €0·0096 cents/l.